1996
DOI: 10.1021/bi960164l
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Spectroscopy of Nitrile Hydratase at pH 7 and 9

Abstract: The iron K-edge X-ray absorption spectrum of Rhodococcus sp. R312 (formerly Brevibacterium sp. R312) nitrile hydratase in frozen solutions at pH 7 and 9 has been analyzed to determine details of the iron coordination. EXAFS analysis implies two or three sulfur ligands per iron and overall six coordination; together with previous EPR and ENDOR results, this implies an N3S2O ligation sphere. The bond lengths from EXAFS analysis [rav(Fe-S) = 2.21 A at pH 7.3; rav(Fe-N/O) = 1.99 A] support cis coordination of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 57 publications
10
105
0
1
Order By: Relevance
“…The other two ligands remain unknown. Previous spectroscopic studies of the active enzyme suggested the coordination of His imidazole ligands at these sites (14,20 (38). Consistently with the crystal structure, the fact that IW11, a minimum peptide segment, does not contain a His residue as well as potential side chains nitrogen donors such as Asn, Gln, and Arg, suggests the coordination of backbone amide nitrogen atoms in IW11.…”
Section: Structure Of the Iron Center Of The Nhase In The Inactive Fosupporting
confidence: 79%
See 1 more Smart Citation
“…The other two ligands remain unknown. Previous spectroscopic studies of the active enzyme suggested the coordination of His imidazole ligands at these sites (14,20 (38). Consistently with the crystal structure, the fact that IW11, a minimum peptide segment, does not contain a His residue as well as potential side chains nitrogen donors such as Asn, Gln, and Arg, suggests the coordination of backbone amide nitrogen atoms in IW11.…”
Section: Structure Of the Iron Center Of The Nhase In The Inactive Fosupporting
confidence: 79%
“…The structure of the iron center in the active form has been studied by various spectroscopies including ESR (3), resonance Raman (13), extended x-ray absorption fine structure (13) and electron nuclear double resonance (14), and the ligand-donor set of N 3 OS 2 has been proposed (14), which is supported by model complexes of the iron center (15)(16)(17). Recently, the metal site structure has been studied in detail by means of electron nuclear double resonance (18), resonance Raman (19), and x-ray absorption (20) spectroscopies. It was demonstrated that the coordination sphere of the metal site consisted of two cis-coordinated sulfhydryl ligands, three His imidazole ligands, and an exchangeable solvent ligand, probably an hydroxo group.…”
mentioning
confidence: 99%
“…Iron-sulfur bond lengths, Fe-S~=2.227(2) A and Fe-$2 = 2.230(2) ~,, are similar to that reported for nitrile hidratase (Fe-S = 2.21 A from the EXAFS data (Scarrow et al, 1996). Ironnitrogen bond lengths in 1, Fe-Nav=l.99,~, are also identical to those in the enzyme.…”
Section: Resultssupporting
confidence: 77%
“…The bond valence sum calculated on the basis of fits shown in Table 2 is in the range (3.7-4.5) found for low-spin ferric complexes (32) (2), which is blue in MeCN and displays a single LMCT band centered at 585(1,975) nm (Table 3). For comparison, azide-bound SOR is blue and has a LMCT band centered at 660(2,300) nm (16).…”
mentioning
confidence: 90%